Women's Representation through Political Parties in Parliament Period of General Election 2019-2024 - Rahmanto, Fajar; Purnomo, Eko Priyo; Kasiwi, Aulia Nur; Salsabila, Lubna (Political Science Program, Universitas Negeri Semarang, 2021)
This research aims to determine women's representation in the DPR RI as a legislative body in Indonesia during the general election in 2019 and determine the factors that influence women's representation in the legislative body. This paper's research method uses a qualitative method with a literature study approach that examines theories, references, and previous scientific literature related to the research object. The findings of the study indicate the level of representation of women in parliament after the holding of the general elections in 2019 has not reached 30%, where the level of representation of women in parliament is still in the number of 20.52% or as many as 118 female legislators and is still dominated by male legislators which reached 457 people or 79.48%. Although it has not reached 30%, the adoption of affirmative policies has led to a significant increase in women's representation in parliament, from 65 women legislators in 2004 to 118 women legislators in the 2019 general election. Political regulation factors with affirmative action and zipper system are two factors that affect women's representation by political parties. Affirmative action mandates every political party participating in the election to pay attention to women's representation of 30% by nominating female candidates for each electoral district. A zipper system requires parties to position at least one woman every three names of candidates. In general elections, political parties present legislation to the legislature. The affirmative action that regulates women's representation's involvement has become the main reason numerous events involve kinship the candidacy.